Osteogenic Ability of Combined Hematopoetic Stem Cell, Hydroxyapatite Graft and Platelet Rich Fibrin on Rats (Rattus Novergicus) - Dwi Rahmawati (Krishna Institute of Medical Sciences “Deemed to be University”, 2017)
Background: In Indonesia, the incidence rate of tooth extraction as the main form of dental treatment reached as high as 79.6% in 2014. Teeth extraction leads to periodontal tissue defect whose treatment, incorporating the use of graft material Hydroxyapatite (HA) and Platelet Rich Fibrin (PRF) with stem cells, has become increasingly widespread. The stem cell potentially put to therapeutic use is the Hematopoetic Stem Cell (HSC). Aim and Objectives: to examine the effect of hematopoetic stem cell addition to HA graft and PRF post-tooth extraction on the number of osteoblasts and amount of Osteoprotegerin (OPG) in periodontal defect treatment. Material and Methods: This study constituted laboratory-based experimental research with a post test-only control group. Twenty four rats (Rattus novergicus) represented the animal study model in this research. Alveolar bone defect in the animal study model was induced by extracting the first molar of the mandible using sterile needle holder clamps. The sample population was divided into four groups: K0: the untreated control group; K1: socket filled with HA Graft and PRF. K2: socket filled with HSC 105 cells. K3: the socket filled with HAGraft and PRF with HSC 106 cells. Results: The K3 group had both the highest number of osteoblasts when compared with the control group (350.17 ± 33.42; P <0.001) and the strongest OPG expression of all treatment groups (11,36 ± 0,54; P <0.01). Conclusion:Acombination of HA graft, PRF and HSC significantly increases the Osteogenic Ability of Combined Hematopoetic Stem Cell, Hydroxyapatite Graft and Platelet Rich Fibrin on Rats (Rattus Novergicus)